2018
DOI: 10.1177/2041669518770691
|View full text |Cite
|
Sign up to set email alerts
|

Magic Circle

Abstract: Full-horizon cylindrical projections of the optic array are in common use. One wonders whether the public actually profits from such pictorial information, since the space behind one’s back does not exist in visual awareness. In an experiment, a test image included six persons located at the corners of an irregular hexagon centred at the camera. Two persons faced the camera, two turned their back to the camera and two others faced a direction at right angles to the camera. The distances to the camera were uneq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This leads to a peculiar inability to deal with full horizon panoramic images, a photographic technique that is rapidly becoming available to the general public. I have shown that this particular mental blindness to the extent of the full optic array applies to virtually all observers (Koenderink, van Doorn, & Wagemans, 2018c).…”
Section: User Interface Elements and Their Effect On Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to a peculiar inability to deal with full horizon panoramic images, a photographic technique that is rapidly becoming available to the general public. I have shown that this particular mental blindness to the extent of the full optic array applies to virtually all observers (Koenderink, van Doorn, & Wagemans, 2018c).…”
Section: User Interface Elements and Their Effect On Behaviourmentioning
confidence: 99%
“…The latter takes training and cognitive “correction” of current awareness, not unlike what one experiences with the classical geometric illusions: One knows what one sees is not right. There is no doubt that one could learn to use such representations in a “right way,” just as there is little doubt that one would still “see them the wrong way” (Koenderink et al., 2018c; Koenderink & van Doorn, 2017).…”
Section: User Interface Elements and Their Effect On Behaviourmentioning
confidence: 99%